Peningkatan Kualitas Data Spasial sebagai Upaya Penyelesaian Sengketa Pertanahan - Yudanto, Danang Cahyo; Mujiburohman, Dian Aries (Kadaster: Journal of Land Information Technology, 2024)
Improving data quality involves enhancing the integrity of land parcel data by organizing and correcting its boundaries to align with actual field conditions. Enhanced spatial data quality, achieved through increased accuracy, completeness, and consistency, plays a crucial role in optimizing land dispute resolution. This study aims to analyze the role of improved spatial data quality in optimizing land dispute resolution. The research method employed is a qualitative approach through a literature review, which gathers information from various sources about data quality and its efforts to enhance land dispute resolution. The results of this study indicate that improving spatial data quality plays a significant role in resolving land disputes by refining land boundaries, reducing overlaps, providing valid ownership evidence, and enabling comprehensive mapping with advanced technology. High-quality data enhances the efficiency of dispute resolution, reducing the required costs and time, and constitutes a strategic step towards creating legal certainty and fair protection of land rights. Keywords: Land Data Quality, Spatial Data, Land Disputes, Systematic Land Registration (PTSL)   INTISARI Peningkatan kualitas data melibatkan peningkatan integritas data bidang tanah dengan menata dan memperbaiki batas-batasnya agar sesuai dengan kondisi sebenarnya di lapangan. Kualitas data spasial yang ditingkatkan, melalui peningkatan akurasi, kelengkapan, dan konsistensi, memiliki peran penting dalam mengoptimalkan penyelesaian sengketa pertanahan. Studi ini bertujuan untuk menganalisis peran peningkatan kualitas data spasial dalam mengoptimalkan penyelesaian sengketa pertanahan. Metode penelitian yang digunakan adalah pendekatan kualitatif melalui literature review, yang mengumpulkan informasi dari berbagai sumber tentang kualitas data dan upayanya dalam meningkatkan penyelesaian sengketa pertanahan. Hasil studi ini menunjukkan bahwa peningkatan kualitas data spasial berperan penting dalam penyelesaian sengketa pertanahan dengan memperbaiki batas tanah, mengurangi tumpang tindih, menyediakan bukti kepemilikan yang valid, serta memungkinkan pemetaan yang menyeluruh dengan teknologi canggih. Dengan data yang berkualitas, efisiensi dalam penyelesaian sengketa juga meningkat, mengurangi biaya dan waktu yang diperlukan, merupakan langkah strategis dalam menciptakan kepastian hukum dan perlindungan hak atas tanah yang adil. Kata Kunci: Kualitas Data Pertanahan, Data Spasial, Sengketa Tanah, PTSL